Lightweight Concrete-on-Steel Composite Beams - McGarraugh, Jay B.; Baldwin, Jr. (Engineering Journal, 1971)
Current design specifications for composite beams include no provisions for beams with lightweight concrete. Conceptually, the use of lightweight concrete for composite beams can lead to greater economy, since a substantial reduction in dead load can be obtained. However, there have been some questions regarding the use of lightweight concrete in composite construction. Six composite beams with lightweight concrete slabs were tested and the results compared with a previously developed theoretical analysis. The theoretical analysis was then used to study the effects of partial shear connection, modular ratio, and unshored construction on the behavior of composite beams.